Genomic Analysis of the DNA Replication Timing Program during Mitotic S Phase in Maize (Zea mays) Root Tips - Wear, Emily E. (Plant Cell, 2017)
All plants and animals must replicate their DNA, using a regulated process to ensure that their genomes are completely and accurately replicated. DNA replication timing programs have been extensively studied in yeast and animal systems, but much less is known about the replication programs of plants. We report a novel adaptation of the “Repli-seq” assay for use in intact root tips of maize (Zea mays) that includes several different cell lineages and present whole-genome replication timing profiles from cells in early, mid, and late S phase of the mitotic cell cycle. Maize root tips have a complex replication timing program, including regions of distinct early, mid, and late S replication that each constitute between 20 and 24% of the genome, as well as other loci corresponding to ∼32% of the genome that exhibit replication activity in two different time windows. Analyses of genomic, transcriptional, and chromatin features of the euchromatic portion of the maize genome provide evidence for a gradient of early replicating, open chromatin that transitions gradually to less open and less transcriptionally active chromatin replicating in mid S phase. Our genomic level analysis also demonstrated that the centromere core replicates in mid S, before heavily compacted classical heterochromatin, including pericentromeres and knobs, which replicate during late S phase.